A Study in Scribal Identification in Fourteenth Century Iceland: A Comparative Philological Analysis of Selected Sections of Holm. Perg. 8vo nr. 10 IX, AM 573 4to, and AM 764 4to - Farrugia, Patrick Aaron, 1992- (2016)
In previous scholarship it has been suggested that Holm. Perg. 8vo nr. 10 IX, AM 573 4to, and Reynistaðarbók AM 764 4to share a common scribal hand. The primary research goal in this study is to either vindicate or challenge the notion of a common scribe using a comparative analysis of paleographic, orthographic, and phonological features. At the behest of the increasing demand for reproducible results in philology, a statistics-based analysis of various features will be employed. I will discuss issues of the amount of paleographic and orthographic changes and variation that we could conceivably see over the course of a scribe’s career, as well as address some of the methodological and epistemological concerns regarding the use and interpretation of philological data. In this thesis, I will argue that it is indeed a single scribe responsible for Holm. Perg. 8vo nr. 10 IX, a fragment of Laxdæla saga, the redaction of Trójumanna saga found in AM 573 4to, and section G of AM 764 4to. There are trends and congruencies in the philological data to support this conclusion, each of which will be discussed individually. Í fyrrum verkum hefur verið lagt til að Holm. Perg. 8vo nr. 10 IX, AM 573 4to, og AM 764 4to hafi svipaða rithönd. Meigin ransóknarmarkmið þessara ritgerðar er að annaðhvort staðfesta eða vefengja þessa tillögu með notkun samanburðargreiningu á skriftarfræðilegum og hljóðfræðilegum þáttum ásamt stafsetningu. Tölfræðileg greining á þessum, ásamt öðrum, þáttum verður notuð sökum aukinna krafa á samkvæmum niðurstöðum í textafræði. Ég mun ræða þann vanda sem fólgin er í því að leggja mat á þær breytingar sem geta átt sér stað á rithönd og stafsetningarvali ritara á æviferli hans. Einnig mun ég tala um þann aðfreðafræðilega vanda sem fylgir greiningu og túlkun textafræðilegra gagna. Ég mun færa rök fyrir því að sami ritari skrifaði Holm. Perg. 8vo nr. 10 IX, brot af Laxdælasögu, útgáfu Trójumanna sögu sem finnst í AM 573 4to og kafla G í AM 764 4to. Loks, mun ég benda á leitni og samræmi í textafræðilegu ...